2021
DOI: 10.1002/jper.21-0339
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor promotes cell‐to‐cell communication in human periodontal ligament stem cells via MAPK and PI3K pathway

Abstract: Background: Cell-cell communication is an essential process to respond to biological stimuli and sustain the micro environmental homeostasis of human periodontal ligament stem cells (hPDLSCs). Connective tissue growth factor (CTGF), a critical secreted matrix protein, exhibits significant tasks in regulating the cellcell and cell-matrix interactions. This study aimed to explore the relationship between CTGF and cell communication and the underlying mechanism. Methods: qRT-PCR was used to detect CCN family, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Intercellular communication mediated by Cx43 can promote the differentiation of ameloblasts and exhibits significant effects on enamel mineralization [ 38 ]. Our previous studies showed that Cx43 was a downstream target protein of CTGF in chondrocytes that regulated cell-to-cell communication [ 27 , 31 ]. Simultaneously, cementocytes specifically express Cx43 as a gap junction carrier to facilitate intercellular communication [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intercellular communication mediated by Cx43 can promote the differentiation of ameloblasts and exhibits significant effects on enamel mineralization [ 38 ]. Our previous studies showed that Cx43 was a downstream target protein of CTGF in chondrocytes that regulated cell-to-cell communication [ 27 , 31 ]. Simultaneously, cementocytes specifically express Cx43 as a gap junction carrier to facilitate intercellular communication [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed demographic information of the enrolled subjects included the following: (1) 12–20 years old, (2) a need to extract premolars due to orthodontic treatment, and (3) those who had any other general diseases or whose teeth had periodontal pockets deeper than 3 mm were excluded from this study. hPDLSCs were cultured as previously described, and periodontal ligament cells were used for subsequent experiments at passages 3–5 [ 31 ]. Alkaline phosphatase, alizarin red and crystal violet staining were used to detect multidirectional differentiation ability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that autophagy, mitogen‐activated protein kinase (MAPK), and phosphatidylinositol‐3 kinase (PI3K)/Akt signaling pathways acted as the downstream pathways of CCN1 in various cellular activities 12,16,17 . Furthermore, CCN1 was proved to be the most expressed protein among CCN1 family in hPDLSCs, but the mechanism by which CCN1 regulates osteogenesis of hPDLSCs remains unclear and needs to be further explored 18 …”
Section: Introductionmentioning
confidence: 99%